INKED - Blount, Jeb (Ascent Audio, 2020)
Learn powerful closing and sales negotiation tactics that unlock yes and seal the deal. Each year, sales professionals leave billions of dollars on the table because they are out gunned, out maneuvered, and out played by savvy buyers, who have been schooled in the art and science of negotiation. Because today's buyers have more power than ever before-more information, more at stake, and more control over the buying process-they almost always enter sales negotiations in a much stronger position than the salespeople on the other side of the table. The results are sadly predictable: salespeople and their companies end up on the losing end of the deal. In this brutal paradigm, if you fail to master the skills, strategies, and tactics to go toe-to-toe with modern buyers and win at the sales negotiation table, your income and long-term earning potential will suffer-along with your company's growth, profits, and market valuation. In his new book INKED, Jeb Blount levels the playing field by giving you the strategies, tactics, techniques, skills, and human-influence frameworks required to become a powerful and effective sales negotiator.